Far-field patterns of metal and dielectric-wall conical horn antennas - Dube P.K.; Singh S.P. (My University, 2025)
Far-field patterns of metal and dielectric-wall conical horn antennas were discussed. The far-field patterns and gain of dielectric-wall conical horn antennas, each with axial length 149.5 cm, flare angle 20.2°, dielectric constant of horn dielectric 2.56, and varying thickness was compared with a metal horn antenna of identical flare angle and axial length at 9.4 GHz in X-band. Results showed that dielectric-wall conical horns offer better performance at acceptable cost.